Afterlives of Chinese communism : political concepts from Mao To xi - Sorace, Christian P., 1981-; Franceschini, Ivan; Loubere, Nicholas (ANU Press ; Verso Books, 2019)
Afterlives of Chinese Communism includes essays from over 50 world-renowned scholars in the China field, from different disciplines, and continents. It provides an indispensable guide for understanding how the intellectual legacies of the Mao era shape Chinese politics today. The volume addresses the question: What lessons does the Chinese Revolution have for leftist thinking in the present? As a volume, the essays speak to each other by answering this question. Across the various approaches, there is a sensitivity to the potentials, enthusiasms, and resistances to domination that Maoist concepts once generated. Each essay provides an introduction to a concept or keyword in Chinese politics, its origins in the Mao era, uses in the present, and potential futures. Participating in an emerging conversation on the futures of communism, the edited volume is designed as an archive of the political vocabulary of Maoism, and a legend to the lost political cartographies of the past and any potential utopian futures.